Model of Sustainable Development of Maramures County During the Pandemic - Izabela RUS; Corina M. RADULESCU; Rita TOADER; Gratiela BOCA; Cezar TOADER; Alina Natalia POP (Communications of International Proceedings, 2021)
This article aims to highlight the importance of choosing a correct strategy for the development of Maramures County in the context of the COVID pandemic. This paper investigates, using several approaches, the possibility to select, based on critical analysis and comparative study, those elements that lead to determining a viable managerial sustainable development “model” for communities in Maramures County, Romania. The current challenges in the conditions of the COVID pandemic of Maramures County mean that more attention must be paid to change management. This can be made easier by using new approaches, tools and more effective methods. The strategic objective for the development of the county will focus on the improvement of living standards and the overall development of the county so that Maramures will become a competitive European region, attractive to tourists and investors, and known for its economic, social and cultural valences. The development strategy of Maramures County must be based on a relevant analysis of the existing conditions of the community. The authors of this paper have analyzed the main indicators of sustainable development of Maramures County in the period 2019 to 2020. The indicators presented in this analysis follow the development stage in Maramures County, in the period 2019-2020, the period of the COVID pandemic. The result is a conceptual integrated model which promotes a balance of interaction between systems—economic, human, environmental and technological—in a dynamic, flexible and functional process.
Keywords: sustainable development; strategy model; analysis resources; economic development.